Diseño y construcción de un micrófono B-format - Gil Vásquez, Alejandro (Ingenierias, 2020)
Currently, different investigations have been developed in 3D audio recording, these investigations seek to corroborate the Ambisonics theory through the constructions of different devices such as B-format microphones and that these can be implemented in different areas such as cinema, television, among others. Due to physical problems such as the size on the arrangement, the distance between capsules and the frequency response of the capsules are no flat, differences can be generated between theory and practice. This final career Project seeks to make the construction of a microphone this type througth 3D design and the use of the four unidirectional capsules Primo 271Y, a measurement has been made with the exponetial sine sweep (ESS) and a digital signal processing, obtaining the characteristics of the B-format microphone through their directivity patterns. Finally, an analysis was carried out when comparing the theorical and practical results, finding a coherent relationship in a certain frequency range